2019
DOI: 10.1111/1346-8138.14765
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of p63, K5 and K7 defines two groups of progenitor cells that differentially contribute to the maintenance of normal sebaceous glands, extraocular sebaceous carcinoma and benign sebaceous tumors

Abstract: The histogenesis of extraocular sebaceous carcinomas is – in contrast to ocular sebaceous carcinomas – unclear, and information about the exact cellular architecture of these lesions and even of the normal sebaceous gland is still scarce. This study attempts to elucidate the histogenesis of sebaceous tumors, using multicolor immunofluorescence stainings to analyze 21 cases of sebaceous tumors (six each of extraocular sebaceous carcinoma, sebaceous adenoma and sebaceoma, and three cases of steatocystomas) and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The results showed that miR-651-5p was expressed at low levels in tumor tissues, while ZEB2 mRNA was highly expressed in tumor tissues ( Figure 1A,1B ). Subsequently, primary SGC cells were isolated from SGC tissues, and the expression of SGC markers (p63, EMA, and CKpan) was verified by western blotting ( 39 , 40 ). The results showed that these markers were strongly expressed in isolated SGC cells (P<0.05 compared with human normal sebaceous gland cell line SZ95 cells, Figure 1C,1D ).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that miR-651-5p was expressed at low levels in tumor tissues, while ZEB2 mRNA was highly expressed in tumor tissues ( Figure 1A,1B ). Subsequently, primary SGC cells were isolated from SGC tissues, and the expression of SGC markers (p63, EMA, and CKpan) was verified by western blotting ( 39 , 40 ). The results showed that these markers were strongly expressed in isolated SGC cells (P<0.05 compared with human normal sebaceous gland cell line SZ95 cells, Figure 1C,1D ).…”
Section: Resultsmentioning
confidence: 99%
“…Such findings in apocrine carcinomas and melanocytic tumors may be due to intracytoplasmic lipid accumulation or lipidization; however, not as a result of the differentiation toward sebocytes. Immunohistochemically, the tumor cells in the present cases of apocrine carcinoma were not similar to sebocytes because the tumor cells were positive for BerEP4 and negative for p63 26–28 . Melanocytic tumors, as in the above cases, also preserve melanocytic differentiation but do not show sebocytic differentiation.…”
Section: Discussionmentioning
confidence: 51%
“…Immunohistochemically, the tumor cells in the present cases of apocrine carcinoma were not similar to sebocytes because the tumor cells were positive for BerEP4 and negative for p63. [26][27][28] Melanocytic tumors, as in the above cases, also preserve melanocytic differentiation but do not show sebocytic differentiation. Thus, labeling the condition as apocrine carcinomas with sebocyte-like cytological features would be more appropriate than apocrine carcinomas with sebaceous differentiation.…”
Section: Casementioning
confidence: 82%
“…Finally, indirect evidence in favour of our model comes from previous studies showing that several glandular epithelia which contain p63 + K5/14 + basal cells do not express p63 in the differentiated glandular compartment (Boecker et al 2019;Daniely et al 2004;Di Como et al 2002;Nylander et al 2002;Signoretti et al 2000). Furthermore, in contrast to the findings in this ASCAP study, low-grade adenosquamous carcinoma/syringomatous tumours of the breast, which contain p63 + and K5/14 + cells, first downregulate p63 and subsequently generate the K8/18 + glandularly differentiated cells via p63-negative K5/14 + intermediary cells indicating a different histogenetic pathway in these lesions compared to ASCAP tumours (Boecker et al 2019;.…”
Section: Discussionmentioning
confidence: 83%